Reaction of rat connective tissue to gutta‐percha and silver points. A long‐term histological study - Holland, Roberto; de Souza, Valdir; Nery, Mauro J.; de Mello, Walderício; Bernabé, Pedro F. E.; Filho, J. A. Otoboni (Wiley, 1982)
Abstract— Silver points and two types of gutta‐percha points were implanted in rat connective tissue. One year later the results were histologically analysed. One type of gutta‐percha point and the silver point were well tolerated by the rat connective tissues. The other type of gutta‐percha point elicited a moderate to severe chronic inflammatory reaction. 1982 Australian Dental Association